2015
DOI: 10.1007/s00580-015-2072-5
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary xanthinuria and urolithiasis in a domestic shorthair cat

Abstract: A 2-year-old domestic shorthair cat was presented with a history of hematuria, stranguria and intermittent urethral obstruction. Urine sediment showed hematuria, pyuria, and yellow-brown, amorphous and spherical crystals. Upon surgical correction of the obstructed urethra by perineal urethrostomy, many dark yellow to grey, irregular, gravel-like to millet grain-sized uroliths, consisting of 100% xanthine by crystallography were found. The urinary xanthine concentration was high. The cat subsequently developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
(42 reference statements)
1
15
0
2
Order By: Relevance
“…Hereditary xanthinuria has been reported in cats (OMIA 001283‐9685), dogs (OMIA 001283‐9615), and cattle (OMIA 001819‐9913) . In some reports, the genetic basis was established by sequencing; in other cases, a primary cause was presumed after eliminating a history of XDH inhibitor use . Similar to the goat in our study, many of the other domestic species with hereditary xanthinuria had severe disease characterized by a juvenile or young adult onset, nephrolithiasis, and renal pathology …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Hereditary xanthinuria has been reported in cats (OMIA 001283‐9685), dogs (OMIA 001283‐9615), and cattle (OMIA 001819‐9913) . In some reports, the genetic basis was established by sequencing; in other cases, a primary cause was presumed after eliminating a history of XDH inhibitor use . Similar to the goat in our study, many of the other domestic species with hereditary xanthinuria had severe disease characterized by a juvenile or young adult onset, nephrolithiasis, and renal pathology …”
Section: Discussionsupporting
confidence: 65%
“…Specifically, a study on sheep with xanthine calculi concluded that low dietary molybdenum could be causative because of molybdenum's role in purine metabolism . Hereditary xanthinuria has been reported in cats (OMIA 001283‐9685), dogs (OMIA 001283‐9615), and cattle (OMIA 001819‐9913) . In some reports, the genetic basis was established by sequencing; in other cases, a primary cause was presumed after eliminating a history of XDH inhibitor use .…”
Section: Discussionmentioning
confidence: 99%
“…A specificity of healthy animals' metabolism is urine saturation with organic and non-organic crystal forming substances, able to form concrements in urolithiasis (1,3,16). Those characteristics provide diagnostically meaningful changes of crystallogenic properties and initiating potential of cat's urine, that was expressed in statistically significant shifting of particular biomedium's "tesiocrystalloscopic pattern", causing abrupt crystal formation activation (P<0,05 -for number of estimated visuametric parameters).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, one of the most common groups of diseases in veterinary medicine is the urinary system pathology (1,2). This fact can be confirmed by increasing number of owners of pets with urolithiasis, looking for help in veterinary clinics (3,4). Urolithiasis is widespread disease, could be found in many species, including cats, dogs, rabbits, guinea-pigs, turtles etc (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation